(untitled) (GYMNASIUM, 2017)
The aim of the present study is to identify the martial arts exercises which to improve the balance and flexibility to the elderly. The research started from the hypothesis that using the psycho-corporal gymnastics exercises (Tam The), it is possible to improve the balance and flexibility to the elderly, which would lead to carry out movements easily, to the prevention of accidents and to the strengthening of health, in general. In this experiment it was included 8 subjects with normal health status, aged between 55 and 60 years. The experiment was carried out over a period of six months, twice a week, one hour per course. The results indicate significant progresses (p<0,05), both as regards the flexibility and balance testing, as a result of the exercises they used. The medium homogeneity of the final values can be explained by relatively heterogeneous initial level and by the duration of the experiment.